(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Plectranthus Amboinicus, plant extract has indispensible beneficial agents in traditional Indian medicine and Ayurveda. Incidence of several diseases, including Hepatocellular carcinoma (HCC) is increasing gradually to a new peak. The major goal of this investigation was to identify and estimate defensive capability of Plectranthus Amboinicus extract on enzymatic functions of liver and to investigate attenuating potential on HCC biomarker. The analyses include, effects of Plectranthus Amboinicus, in serum level of AST,ALT,ALP, Total bilirubin, and alpha fetoprotein (AFP) fluctuations in carbon tetrachloride (CCL4), induced HCC rats. Toxicity was stimulated by CCL4 with olive oil as vehicle in the ratio of (1:1 v/v);( olive oil 5mL/kg i.p). Sylimarin was used as a reference (standard) for intoxicated animal groups. Moreover, observation of histological studies favours the biochemical changes observed. Results showed P.Amboinicus, is highly potential in depleting the level of liver enzymes and AFP biomarker, based on dose regimen. These might have been due to the action of enriched phenolic content of P.Amboinicus, to get rid of free radicals. Study concluded that P.Amboinicus is a universal medicine and modulating biochemical changes in hepatotoxicity of liver cells induced HCC rat model.